2022
DOI: 10.1186/s12891-022-05845-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical markers associations with pain, symptoms, and disability compared to radiographic severity in knee osteoarthritis patients: a secondary analysis from a cluster randomized controlled trial

Abstract: Background Conventional radiography is commonly used to diagnose knee osteoarthritis (OA), but also to guide clinical decision-making, despite a well-established discordance between radiographic severity and patient symptoms. The incidence and progression of OA is driven, in part, by biomechanical markers. Therefore, these dynamic markers may be a good metric of functional status and actionable targets for clinicians when developing conservative treatment plans. The aim of this study was to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…For example, Fukutani et al performed multivariable regression analyses to adjust for confounding factors and reported that VT rated by experts was independently associated with the Japanese Knee Osteoarthritis Measure score (a type of PROMs) [ 15 ]. Additionally, Bensalma et al found that a larger VT assessed quantitatively using the varus angle during the stance phase measured using a three-dimensional motion analysis system was associated with lower KOOS scores [ 19 ]. However, several other reports did not find an association between VT and PROMs [ 9 , 12 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Fukutani et al performed multivariable regression analyses to adjust for confounding factors and reported that VT rated by experts was independently associated with the Japanese Knee Osteoarthritis Measure score (a type of PROMs) [ 15 ]. Additionally, Bensalma et al found that a larger VT assessed quantitatively using the varus angle during the stance phase measured using a three-dimensional motion analysis system was associated with lower KOOS scores [ 19 ]. However, several other reports did not find an association between VT and PROMs [ 9 , 12 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the KOOS scores, significant associations with VT were found for the pain, symptoms, and ADL scores after adjusting for potential confounders, but not for the Sport and QoL scores in this study. The study by Bensalma et al also showed that larger VT was associated with lower pain, symptoms, and ADL KOOS scores [ 19 ]. These results agree with our results, although the Sport and QoL scores were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 There may also be varying degrees of muscle pathology, a high rate of muscle protein degradation and muscle volume losses, related problems that stem from damage or dysfunction of the joint sensory and motor nerves, muscle inhibition and/or weakness, plus evidence of increasing postural instability in weight bearing joints. [31][32][33][34][35][36][37] In addition, an immense loss of functional independence, motivation for self-care, a loss of independence, and a declining belief in their ability to overcome their life challenges are cognitive factors that may be expected to increasingly exacerbate the older adults pain, 38 and overall multiple biomechanical disease impacts. 39 As such, if an older adult suffering from various degrees of osteoarthritis wants to remain in the community, rather than reside in a nursing home, their goals can probably only be met if concerted efforts are made to assess if this is feasible, for example if they have mild-moderate rather than severe forms of the disease, and if so to carefully and insightfully assess their past medical history, and current health and disease status, and address and plan for their immediate, short term and long term needs accordingly, bearing in mind the more recently acknowledged need to keep older adults as healthy as possible and protected against COVID infections and their oftentimes dire repercussions.…”
Section: Osteoarthritismentioning
confidence: 99%